The Performance of Hematological Parameters for Diagnosis of Acute Appendicitis in Children - Supangat Supangat; Akhmad Makhmudi; Azka Darajat; Elly Nurus Sakinah; Muhammad Yuda Nugraha; Achmad Ilham Tohari; Tegar Syaiful Qodar; Bagus Wahyu Mulyono (Journal of Agromedicine and Medical Sciences, 2022)
Early diagnosis of pediatric appendicitis is still difficult to make and 30-40% of cases do not show typical classic symptoms. The negative appendectomy rate and the risk of perforation reach 20% so that new, easy, inexpensive and accurate additional examination is needed. This study aimed to compare platelet distribution width (PDW) and mean platelet volume (MPV) values of appendicitis and control patients. This study is retrospective case control study. Differences in MPV and PDW levels in patients with appendicitis and controls were analyzed with a t-test and determination of sensitivity, specificity and accuracy of the two markers in appendicitis diagnosis were performed by ROC analysis The mean MPV appendicitis was significantly lower (p <0.05) compared to controls (8.3 ± 1.9; 9.2 ± 1.5) while PDW of appendicitis patients did not differ significantly from controls (10.4 ± 1, 4, 10.7 ± 2.4; p> 0.05). AUC MPV as a diagnostic tool for appendicitis 0.619 with a normal limit of 6.6 fl has a sensitivity of 90% and specificity of 30%. MPV can be used for the diagnosis of appendicitis with a normal limit of 6.6 fl having a sensitivity of 90% and specificity of 30%. There was no significant difference between PDW of appendicitis patients with controls. There was no significant difference between MPV levels of patients with simple appendicitis and complications. Keywords: Appendicitis, MPV, PDW, Platelet